18.77 % Efficiency Organic Solar Cells Promoted by Aqueous Solution Processed Cobalt(II) Acetate Hole Transporting Layer. Issue 41 (6th September 2021) - Meng, Huifeng; Liao, Chentong; Deng, Min; Xu, Xiaopeng; Yu, Liyang; Peng, Qiang
Abstract: A robust hole transporting layer (HTL), using the cost‐effective Cobalt(II) acetate tetrahydrate (Co(OAc)2 ⋅4 H2 O) as the precursor, was simply processed from its aqueous solution followed by thermal annealing (TA) and UV‐ozone (UVO) treatments. The TA treatment induced the loss of crystal water followed by oxidization of Co(OAc)2 ⋅4 H2 O precursor, which increased the work function. However, TA treatment differently realize a high work function and ideal morphology for charge extraction. The resulting problems could be circumvented easily by additional UVO treatment, which also enhanced the conductivity and lowered the resistance for charge transport. The optimal condition was found to be a low temperature TA (150 °C) followed by simple UVO, where the crystal water in Co(OAc)2 ⋅4 H2 O was removed fully and the HTL surface was anchored by substantial hydroxy groups. Using PM6 as the polymer donor and L8‐BO as the electron acceptor, a record high PCE of 18.77 % of the binary blend OSCs was achieved, higher than the common PEDOT:PSS‐based solar cell devices (18.02 %). Abstract : A robust hole transporting layer based on cobalt(II) acetate was developed by aqueous solution processing technology, low temperature thermal annealing and UV‐ozone treatment, which enabled a record high‐power conversion efficiency of 18.77 % of binary blend organic solar cells.